Impact of Agile Supply Chain Management (ASCM) on Competitive Priorities (CP ) (An Empirical Study in Al-Narjis Plastic Pipes Factory in Basra - Al-Hassan , Rafid (The Gulf Economist, 2022)
The objective of the current study was to try to test and diagnose the impact of agile supply chain management on competitive priorities, in an attempt by the researcher to enrich the knowledge literature in explaining the relationship between those variables according to the empirical study approach of the Narjis Plastic Pipe Factory in Basraا. The data related to the applied framework of the study were collected through a checklist developed based on solid references for studies related to the variables of our current study, and the tool was subjected to statistical validity and reliability tests. The problem of the study was represented in the existence of a knowledge and procedural gap about the conceptual foundations of agile supply chain management, which has not yet risen to the level of theory. It is limited to focusing on that management in a partial perspective, as it cannot be approached as more than a marketing approach that is not an academic approach. The study reached a set of statistical results represented in the existence of a positive and medium correlation between agile supply chain management and competitive priorities, and there is a strong impact of agile supply chain management on competitive priorities. Based on the results that have been reached, a number of recommendations were suggested.